DIFFERENTIATED METHODS OF GENERAL AND SPECIAL TRAINING OF YOUNG ROAD CYCLISTS AT THE INITIAL STAGE OF SPECIALIZATION - Kholmuratov, O. Yu. (Educational Research in Universal Sciences, 2023)
The article presents a methodology for the expediency of constructing the dynamics of training and competitive loads in the process of training cyclists of primary sports specialization at the age of 13-14, both for the conditions of sports training and for competitions.